Effect of Saccharomyces cerevisiae Supplementation to Paddy Straw Based Substrate on in Vitro Rumen Fermentation Parameters - Elanthamil, R.; Bandeswaran, C.; Bharthidhasan, A.; Valli, C. (Indian Journal of Animal Nutrition, 2018)
The Saccharomyces cerevisiae was supplemented to the substrate containing paddy straw (60%) and concentrate mixture (40%) at various doses viz., 0.0 (control), 0.5 × 106, 0.5 × 107 and 0.5 × 108 CFU. The in vitro true dry matter degradability, total gas production, volatile fatty acid production and microbial population increased proportionally to the dose of S. cerevisiae. However, methane production was not affected significantly. The ruminal pH and ammonia nitrogen levels decreased (P